IMS 552: Information Systems Management. Group Assignment: RTM Kelantan / Aliff Danial Amran Suhaimi … [et al.] - Amran Suhaimi, Aliff Danial; Che Hussin, Che Siti Nadia; Mohammad Nasir, Farhah; Ramli, Nurhasna (2015)
This project is about how the system that runs at RTM Kelantan smoothly. The system in RTM Kelantan mostly focused on writing and publishing news on radio and television and RTM Kelantan also have its own broadcasting which is known as Kelantan FM. This project also will evaluate how the process of broadcasting is running and how they can broadcast the live news from the Angkasapuri.